Assessment of toxic mechanisms and mode of action to three different levels of species for 14 antibiotics based on interspecies correlation, excess toxicity, and QSAR. (March 2023) - Li, Jin J.; Yue, Ya X.; Jiang, Jie F.; Shi, Sheng J.; Wu, Hui X.; Zhao, Yuan H.; Che, Fei F.
Abstract: Antibiotics have received much attention owing to their ecotoxicity toward nontarget aquatic creatures. However, the mode of action (MOA) of toxicity against nontarget organisms is unclear in some aquatic organisms. In this study, the comparison of toxicities through interspecies correlations, excess toxicity calculated from toxicity ratio, and quantitative structure-activity relationship (QSAR) was carried out to investigate the MOAs for 14 antibiotics among Daphnia magna, Vibrio fischeri, and Pseudokirchneriella subcapitata . The results showed that interspecies toxicity correlations were very poor between any two of the three species for the 14 antibiotics. The toxicity ratio revealed that most antibiotics exhibited excess toxicity to algae and Daphnia magna but not to V. fischeri, demonstrating that some antibiotics share the same MOA, but some antibiotics share different MOAs among the three different levels of species. P. subcapitata was the most sensitive species, and V. fischeri was the least sensitive species. This is because of the differences in the biouptake and interactions of antibiotics with the target receptors between the three different trophic levels of the species. Molecular docking simulations suggested that the toxicity of antibiotics depends highly on their interactions with target receptors through hydrogen bonds, electrostatic or polar interactions, π bond interactions, and van der Waals forces. QSAR models demonstrated that hydrogen bonding and electrophilicity/nucleophilicity play key roles in the interaction of antibiotics with different receptors in the three species. The toxic mechanisms of antibiotics are attributed to the interactions between electrophilic antibiotics and biological nucleophiles, and hydrogen-bond interactions. These results are valuable for understanding the toxic mechanisms and MOA of the three different levels of species. Graphical abstract: Image 1 Highlights: Most of antibiotics exhibit excess toxicity to algae, but not to V. fischeri. Mode of action (MOA) of antibiotics is species-dependent for different species. Differences in bio-uptake and ligand-receptor interaction result in different MOAs. Hydrogen bonding and electrophilicity play key roles in ligand-receptor interaction. Interspecies correlation is improved by adding molecular descriptors into equations.